Typical Kawasaki Disease Presenting With Pancreatitis and Bilateral Parotid Gland Involvement: A Case Report and Literature Review - Botti, Matteo; Costagliola, Giorgio; Consolini, Rita (Frontiers in Pediatrics, 2018)
We describe the case of a 3-year child in which pancreatic and parotid gland involvement preceded the development of the classical clinical phenotype of a typical Kawasaki Disease (KD). The child was referred to the Emergency Department with a story of 3-days continuous fever associated with abdominal pain and bilaterally swelling in the parotid regions; laboratory evaluation identified markedly increased levels of total amylase, pancreatic amylase, lipase and transaminase, and diagnosis of pancreatitis was posed. After 9 days of fever and persistence of the clinical features, the classical signs of KD appeared, and the child was treated with intravenous immunoglobulins (IVIG), showing a dramatic response with complete resolution of the clinical picture. In this work we reviewed the literature about gastrointestinal symptoms in KD, focusing on pancreatic and hepatic involvement. This analysis highlighted that, in case of fever associated with pancreatic inflammation, KD must be considered in the spectrum of differential diagnosis, and that gastrointestinal involvement in KD is frequently associated with an incomplete response to IVIG treatment.